Multifunctional near-infrared light-triggered biodegradable micelles for chemo- and photo-thermal combination therapy - Cao, Jie (Oncotarget, 2016)
A combination of chemo- and photo-thermal therapy (PTT) has provided a promising efficient approach for cancer therapy. To achieve the superior synergistic chemotherapeutic effect with PTT, the development of a simple theranostic nanoplatform that can provide both cancer imaging and a spatial-temporal synchronism of both therapeutic approaches are highly desired. Our previous study has demonstrated that near-infrared (NIR) light-triggered biodegradable chitosan-based amphiphilic block copolymer micelles (SNSC) containing light-sensitive 2-nitrobenzyl alcohol and NIR dye cypate on the hydrophobic block could be used for fast light-triggered drug release. In this study, we conjugated the SNSC micelles with tumor targeting ligand c(RGDyK) and also encapsulated antitumor drug Paclitaxel (PTX). The results show that c(RGDyK)-modified micelles could enhance the targeting and residence time in tumor site, as well as be capable performing high temperature response for PTT on cancer cells and two-photon photolysis for fast release of anticancer drugs under NIR irradiation. In vitro release profiles show a significant controlled release effort that the release concentration of PTX from micelles was significantly increased with the exposure of NIR light. In vitro and in vivo antitumor studies demonstrate that, compared with chemo or PTT treatment alone, the combined treatment with the local exposure of NIR light exhibited significantly enhanced anti-tumor efficiency. These findings indicate that this system exhibited great potential in tumor-targeting imaging and synchronous chemo- and photo-thermal therapy.